Feasibility of digital healthcare in enhancing healthcare access in semiurban areas of Karachi, Pakistan: a qualitative descriptive study - Frances Griffiths; Romaina Iqbal; Bronwyn Harris; Narjis Rizvi; Rawshan Jabeen (BMJ Open)
Objective Our research aimed to assess the feasibility of digital health in enhancing healthcare access in the semiurban areas of Karachi, Pakistan.Study design and setting This qualitative descriptive study was employed at three villages in Gadap, Karachi, Pakistan, with varying socioeconomic contexts, using a feasibility framework. Ethical approval was provided by the Ethical Review Committee (ERC) of The Aga Khan University.Study participants Through purposive sampling, demand and supply-side stakeholders (N=152) were invited to participate in the study, including community leaders, activists and members, representatives from non-governmental organisations, public and private sector healthcare providers, and digital healthcare providers and experts. Both inductive and deductive approaches were used for data analysis.Measure of outcomes The assessment of feasible demand-side and supply-side factors would be extremely useful in the planning and implementation of a sustainable digital health programme.Results Digital health is an acceptable and practically feasible option and is a potential solution to enhance healthcare access and equity, particularly in semiurban and rural remote areas, where healthcare access is limited. Digital healthcare should not replace inperson healthcare but should instead be offered in combination with it, preferably through a ‘Hub & Spoke Model’ facility. Few challenges exist in implementing digital health, including privacy, ethical issues, lack of evidence-based standards, inadequate training of healthcare providers, technological barriers and access to digital health services by vulnerable populations, such as the elderly, women, individuals who are illiterate and those of low-income class.Conclusion Our study concludes that digital healthcare is a dire need and is a potential solution to enhance healthcare access and equity, as it is acceptable and practically feasible. A mix of inperson and digital health consultation should be offered through a hub and spoke model. Few challenges to implementing digital health exist and should be addressed by tailoring digital health through co-creation and engaging all stakeholders.